Pengaruh Kinerja Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2018-2022 - Elis Juliyanti Mausali; Pius Bumi Kellen; Siprianus G. Tefa (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Stock returns are the results obtained from stock investments. Financial performance is said to have a big influence on stock returns, therefore it is necessary to pay attention to information and carry out an analysis of the condition of the company's financial statements using financial ratios. The aim of this research is to determine the influence of Liquidity, Leverage, Activity and Profitability on stock returns both partially and simultaneously. The company population in this study was 15 companies and 65 samples, using secondary data and purposive sampling techniques with the results of annual financial reports of manufacturing companies in various industrial sectors listed on the BEI for the 2018-2022 period. Data analysis in this research uses descriptive analysis, classical assumption tests consisting of data normality tests, multicollinearity tests, autocorrelation tests and heteroscedasticity tests, multiple regression tests and hypothesis tests consisting of t tests, F tests and coefficient of determination tests. Based on the results of this research, it shows that liquidity and leverage have a significant effect on stock returns. Activity and profitability have no effect on stock returns. And Liquidity, Leverage, Activity and Profitability simultaneously have a significant effect on stock returns.